Caffeic acid phenethyl ester up-regulates antioxidant levels in hepatic stellate cell line T6 via an Nrf2-mediated mitogen activated protein kinases pathway - Yang, Ning; Shi, Juan-Juan; Wu, Feng-Ping; Li, Mei; Zhang, Xin; Li, Ya-Ping; Zhai, Song; Jia, Xiao-Li; Dang, Shuang-Suo (World journal of gastroenterology : WJG, 2017)
AIM To investigate the antioxidant effect of caffeic acid phenethyl ester(CAPE) in hepatic stellate cell-T6(HSC-T6) cells cultured in vitro and the potential mechanisms.METHODS HSC-T6 cells were cultured in vitro and treated with various concentrations of CAPE for 24, 48 and 72 h, respectively. Cell proliferation was investigated using the MTT assay, and cell ultrastructural alterations were observed by transmission electron microscopy. Flow cytometry was employed to investigate the effects of CAPE on apoptosis and the levels of reactive oxygen species in HSC-T6 cells cultured in vitro. An enzyme immunoassay instrument was used to evaluate antioxidant enzyme expression. The effect on α-smooth muscle actin was shown using immunofluorescence. Gene and protein levels of Nrf2, related factors, and mitogen activated protein kinases(MAPKs), in HSC-T6 cells were detected using RT-PCR and Western blot, respectively.RESULTS CAPE inhibited the proliferation and activation of HSC-T6 cells cultured in vitro. CAPE increased the antioxidant levels and the translocation of Nrf2 from the cytoplasm to the nucleus in HSC-T6 cells. Moreover,the phosphorylation of MAPKs in cells decreased in response to CAPE. Interestingly, CAPE-induced oxidative stress in the cells was significantly attenuated by pretreatment with MAPKs inhibitors.CONCLUSION CAPE inhibits cell proliferation and up-regulates the antioxidant levels in HSC-T6 cells partly through the Nrf2-MAPKs signaling pathway.